Care needs and satisfaction with nursing care quality of cancer patients - AKMAN, MEHMET (My University, 2022)
Abstract – Objective: This study aims to determine the relationships between care needs and satisfaction with nursing care quality of chemotherapy-treated cancer patients. Patients and Methods: This cross-sectional study was conducted between November and December 2021 in an Outpatient Chemotherapy Unit in Istanbul. The interview form consists of sociodemographic and treatment-related questions, cancer needs of patients, the satisfaction with the quality of nursing care. Results: Most of the participants were 55 years of age and older (61%), women (57.8%), had comorbid diseases (52.4%), and 48% were diagnosed with stage II cancer (48%). The care needs to be reported frequently by patients were mostly psychological and interpersonal communication. It was determined that the most important variables that increased the health care needs were perception by patients of their health status, age, stage of cancer, and the level of satisfaction they perceive together with the quality of nursing care. Conclusions: This study determined that patient care should be planned based on the factors affecting patient care needs and that care needs could decrease with increasing satisfaction with nursing care.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Nursing Care; Quality of care; Patient satisfaction; Cancer needs; Cross-sectional studies; OF-LIFE; QUESTIONNAIRE; PEOPLE; Nursing Care; Quality of care; Patient satisfaction; Cancer needs; Cross-sectional studies